Rancang Bangun Sistem Informasi Pemasaran Barang Antik Berbasis Mobile Web - Rofiqoh Dewi; Abdul Muis (LPPM Universitas Potensi Utama, 2023)
In this era of digitalization, the use of technology in developing a product is very commonly used to introduce products, sell products and other things related to recognizing product needs such as product information, product functionality, price, or uniqueness that a product has but is not found in other products. like antiques. Currently, it is very rare to find the marketing of antiques in modern and traditional markets. The need to buy antiques is also very rare, but that doesn't mean it has disappeared with time because there are still some people who are interested in antiques if they appear displayed in a window at the market. Based on this, to make it easier for people to access antiques, technology is needed to be able to process data well to make it more efficient and effective. Based on this, the direction of the research carried out by the researcher aims to introduce antiques to all levels of society and build a mobile website to market these antiques so that people can get to know the types and benefits of antiques, the history of antiques and the prices of these antiques.